Upaya Meningkatkan Kemampuan Berhitung Siswa Kelas III Pada Materi Pengurangan Dengan Meminjam Melalui Media Konkret - Amoy Nanda Lumintang; Ratih Puspita Dewi (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Learning is a process of change for each individual, both in knowledge and attitudes. Every individual after learning will experience changes in their life. When studying at school, teachers only tend to teach students to memorize, read and calculate. Teachers have an important task in the learning process in class to improve students' learning abilities and understanding of the material provided. Based on observations made by the author, at SD N Pajang 3 teachers tend to be monotonous and use the same learning methods every day so that students quickly get bored and have difficulty understanding the material, especially in mathematics lessons. Based on the researcher's observations during the learning process in class 3, especially in mathematics, it was proven that many students did not understand so that based on test scores students got a score of 60. This research uses a qualitative approach which aims to determine the improvement in learning outcomes of class 3 students at SD N Pajang 3 before and after carrying out learning using concrete media. This research was conducted descriptively, namely by providing a pretest and posttest. Based on the results of this research, it was concluded that the use of concrete media had a positive impact and was effectively used in improving students' addition skills.